Effect of glass addition on the properties of CaCu3Ti4O12 ceramics - Julie Juliewatty Mohamed; Mohd Fariz Ab Rahman; Mohd Fadzil Ain; Zainal Arifin Ahmad (Trans Tech Publications, 2016)
The effect of glass addition on the properties of CaCu3Ti4O12 (CCTO) ceramics was studied. CCTO ceramics with BaO-SrO-Nb2O5-B2O3-SiO2 (BSNBS) glass additive were prepared using solid state reaction method. The raw materials of CCTO and BSNBS were wet mixed separately for 24 hours, dried overnight and subsequently the BSNBS powders was melted at 1450°C for 2 hours while CCTO powders was calcined at 900°C for 12 hours. BSNBS glass then was grinded to form a fine powders. Different weight percentages of BSNBS powder were added into CCTO and the powders were wet mixed at 24 hours. The mixtures were dried, compacted at 250 MPa and then sintered at 1050°C for 10 hours. X-Ray Diffractometer (XRD) analysis showed the formation of CCTO phase for all sintered samples while secondary phase of CuO phase was identified for sintered BSNBS 1.0 sample. Observation on Scanning Electron Microscopy (SEM) micrographs showed abnormal grain growth was seen in CCTO sample and grain size of the samples become finer with increasing the concentration glass addition. CCTO sample obtained the highest dielectric constant (8670) while the lowest dielectric loss (0.38) was recorded by BSNBS 0.10 sample, measured at 1 MHz.